2009
DOI: 10.1378/chest.08-1997
|View full text |Cite
|
Sign up to set email alerts
|

Simulation System for a Rebreathing Technique To Measure Multiple Cardiopulmonary Function Parameters

Abstract: Background We developed a simple method for simulating a rebreathing maneuver to test the accuracy of the apparatus for simultaneous measurement of lung volume, diffusing capacity of the lung for carbon monoxide (DLCO), diffusing capacity of the lung for nitric oxide (DLNO), and pulmonary blood flow (Q.c). Methods A test gas mixture containing 0.3% methane, 0.3% CO, 0.8% acetylene, 30% O2, and 40 ppm nitric oxide in balance of nitrogen was sequentially diluted with a rebreathing gas mixture containing 0.3% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Using high-resolution computer tomography at two inflation pressures and the deformation analysis, the same group showed that the remaining lobes had non-uniform regional mechanical strains. Two growth phases were identified: (i) an initial rapid proliferative phase, characterized by air space and blood volume increases, and (ii) a progressive remodeling phase, characterized by tissue relaxation and increased lung compliance persisting over several months (Hsia et al, 2008;Yilmaz et al, 2009).…”
Section: Mechanical Stimuli In Lung Regenerationmentioning
confidence: 99%
“…Using high-resolution computer tomography at two inflation pressures and the deformation analysis, the same group showed that the remaining lobes had non-uniform regional mechanical strains. Two growth phases were identified: (i) an initial rapid proliferative phase, characterized by air space and blood volume increases, and (ii) a progressive remodeling phase, characterized by tissue relaxation and increased lung compliance persisting over several months (Hsia et al, 2008;Yilmaz et al, 2009).…”
Section: Mechanical Stimuli In Lung Regenerationmentioning
confidence: 99%